Rejuvenation of stellar mergers and the origin of magnetic fields in massive stars - Schneider, F; Podsiadlowski, P; Langer, N; Castro, N; Fossati, L (Oxford University Press, 2016)
Approximately 10 per cent of massive OBA main-sequence (MS) and pre-MS stars harbour strong, large-scale magnetic fields. At the same time, there is a dearth of magnetic stars in close binaries. A process generating strong magnetic fields only in some stars must be responsible with the merging of pre-MS and MS stars being suggested as one such channel. Stars emerging from the coalescence of two MS stars are rejuvenated, appearing younger than they are. They can therefore be identified by comparison with reference clocks. Here, we predict the rejuvenation of MS merger products over a wide range of masses and binary configurations calibrated to smoothed-particle-hydrodynamical merger models. We find that the rejuvenation is of the order of the nuclear time-scale and is strongest in the lowest mass mergers and the most evolved binary progenitors with the largest mass ratios. These predictions allow us to put constraints on the binary progenitors of merger products. We show that the magnetic stars HR 2949 and τ Sco are younger than the potential binary companion HR 2948 and the Upper-Sco association, respectively, making them promising merger candidates. We find that the age discrepancies and the potential binary progenitors of both are consistent with them being rejuvenated merger products, implying that their magnetic fields may originate from this channel. Searching for age discrepancies in magnetic stars is therefore a powerful way to explore which fraction of magnetic stars may have obtained their strong magnetic field in MS mergers and to improve our understanding of magnetism in massive stars and their remnants.